Form and Substance in US, English, New Zealand and Japanese Law: A Framework for Better Comparisons of Developments in the law of Unfair Contracts - Nottage, Luke (Victoria University of Wellington Law Review, 1996)
There was talk of change in the law of contract in the United States, England, New Zealand and Japan in the 1990s. Often this was linked to broader trends of internationalisation. This article builds on the "form-substance" framework proposed by Atiyah and Summers, focusing on the fine print doctrine, the duty of good faith, and the law of unconscionability and undue influence. It argues that developments in these areas of contract law, which control unfair contracts, tend to be consistent with the overall orientation of each national legal system. This suggests that counter-systemic developments in each legal system's contract law will be met by more resistance than expected. Further, those overall orientations are not necessarily convergent, and this is likely to affect the impact of international developments in contract law on each legal system.